2021
DOI: 10.1038/s41598-021-03245-4
|View full text |Cite
|
Sign up to set email alerts
|

SARS-CoV-2 infection reduces human nasopharyngeal commensal microbiome with inclusion of pathobionts

Abstract: The microbiota of the nasopharyngeal tract (NT) play a role in host immunity against respiratory infectious diseases. However, scant information is available on interactions of SARS-CoV-2 with the nasopharyngeal microbiome. This study characterizes the effects of SARS-CoV-2 infection on human nasopharyngeal microbiomes and their relevant metabolic functions. Twenty-two (n = 22) nasopharyngeal swab samples (including COVID-19 patients = 8, recovered humans = 7, and healthy people = 7) were collected, and under… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
55
1

Year Published

2022
2022
2023
2023

Publication Types

Select...
8
1

Relationship

4
5

Authors

Journals

citations
Cited by 40 publications
(61 citation statements)
references
References 60 publications
5
55
1
Order By: Relevance
“…COVID-19 diagnosis, laboratory testing, and treatment in this cohort have been previously described ( 30 ). Patients with confirmed COVID-19 were classified as having mild/moderate (MM) or severe/critical (SC) disease based on symptomatology ( 22 ).…”
Section: Methodsmentioning
confidence: 99%
“…COVID-19 diagnosis, laboratory testing, and treatment in this cohort have been previously described ( 30 ). Patients with confirmed COVID-19 were classified as having mild/moderate (MM) or severe/critical (SC) disease based on symptomatology ( 22 ).…”
Section: Methodsmentioning
confidence: 99%
“…Emerging evidence has suggested that the pathology of severe acute respiratory syndrome coronavirus 2 (SARS‐CoV‐2) may in part be explained by microbial species, 1 contributing to the inflammatory phenotype commonly seen in patients with coronavirus disease (COVID‐19). 2 , 3 Indeed, dysbiosis of the gut microbiota has been associated with poor clinical outcomes in mechanically ventilated COVID‐19 patients. Specifically, Wu et al observed elevated Granulicatella and Rothia mucilaginosa in the gut microbiome of COVID‐19 hospitalized patients when compared to healthy individuals.…”
Section: Figurementioning
confidence: 99%
“…Coronaviruses [206][207][208] Depression [209,210] Diabetes [211,212] Diarrheal Diseases [213][214][215] Epilepsy [216,217] Fibromyalgia Syndrome [218,219] Fungal Infections [220] Headache Disorders [221] HIV and AIDS [222,223] Inflammatory Bowel Disease (Crohn's Disease and Ulcerative Colitis) [224,225] Irritable Bowel Syndrome [226,227] Lung Cancer [228,229] Melanoma [230,231] Metabolic Syndrome [232,233] Multidrug-Resistant Bacterial Infections [234,235] Multiple Sclerosis [236,237] Myalgic Encephalomyelitis/ Chronic Fatigue Syndrome [238,239] Neurologic Cancer [240,241] Nonalcoholic Fatty Liver Disease [242,243] Obesity [244,245] Pain [246,247] Pancreatic Cancer [248,249] Parkinson's Disease [250,…”
Section: Disease Evidence Of Microbiome Involvementmentioning
confidence: 99%